The family records of Andreas de Pozza from 1569-1603 - Janeković-Roemer, Zdenka (Array, 2009)
Summary: The Privata series of the Dubrovnik State Archives contains several dozens of private and business books of the Dubrovnik nobility and merchants from the fifteenth and the sixteenth centuries. Even though the majority of such private books have been lost, the ones that have been preserved represent an important fund for the research of business matters and family life of Dubrovnik residents in the Middle Ages and in the Early Modern Times. The article deals mainly with the family chronicle of Andreas de Pozza, son of Antonius, which had been kept between 1569 and 1603